2017
DOI: 10.13057/biofar/f140205
|View full text |Cite
|
Sign up to set email alerts
|

The safety of tea agarwood (Aquilaria malaccensis) from tree induction through test of toxicity subchronic oral 90 days

Abstract: Batubara R, Surjanto, Sihombing TM, Ginting H. 2016. The safety of tea agarwood (Aquilaria malaccensis) from tree induction throuht test of toxicity subcronic oral 90 days. Biofarmasi 14: 69-76. Subchronic toxicity test is a test to detect the toxic effect that arises after the administration of the test reparation with repeated doses were given orally to the tested animal for 28 or 90 days. Leaves agarwood (Aquilaria malaccensis Lamk) is a tree from a tribe Thymeleaceae, already started popular used the farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Generally, AM leaves aqueous extract administration is considered safe and the AM dosage should not cause any negative effects on sperm. Previous study indicated that AM leaves extract administration up to 520 mg kg −1 daily for 90 days in male mice does not cause any toxic signs and symptoms and is safe for consumption (61). The LD50 of the leaf extract was also found to be above 2000 mg kg −1 (62).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, AM leaves aqueous extract administration is considered safe and the AM dosage should not cause any negative effects on sperm. Previous study indicated that AM leaves extract administration up to 520 mg kg −1 daily for 90 days in male mice does not cause any toxic signs and symptoms and is safe for consumption (61). The LD50 of the leaf extract was also found to be above 2000 mg kg −1 (62).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the n-hexane extract exhibited weak antioxidant compounds with a total phenol of 0.45% (Wahyuningrum et al 2018). Batubara et al (2018) conducted studies on acute and subchronic toxicity tests (Batubara et al 2016), revealing that agarwood tea was safe for consumption. However, leaf utilization needs further investigation to advance development, especially regarding raw material variations.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwood leaves contain chemical compounds such as flavonoids, flavones, flavonols, and isoflavones. These chemical compounds are categorized as antioxidant sources (Surjanto et al 2015), and safe for consumption (Batubara et al 2016).…”
Section: Introductionmentioning
confidence: 99%